Step-by-step explanation:
q=r+rst
Rewrite the equation as
r+rst=q
Subtract r from both sides of the equation.
r st=q−r
Divide each term by rt
(r st )/rt=(q/rt)−(r/rt)
Cancel the common factor.
(
s=(q/rt)−1/t
The answer is going to be A
Answer:
easey, sub them
(x,y)
see if true
(0,1), 2(0)+1>-4, 1>-4, true
(4,-12), 2(4)+-12>-4, 8-12>-4, -4>-4, false
(5,-12), 2(5)+-12>-4, 10-12<-4, -2>-4, true
(-1,-1), 2(-1)+-1>-4, -2-1>-4, -3>-4, true
(-3,0), 2(-3)+0>-4, -6>-4, false
answers are
(0,1)
(5,-12)
(-1,-1)
Hopefully that helped you a little bit :)